Small Clauses in Advertisements in a Discursive-Functional Perspective - Pezatti, Erotilde Goreti [UNESP] (Univ Federal Fluminense, 2018)
This study aims at analyzing small clause from Functional-Discourse Grammar viewpoint (Hengeveld and Mackenzie 2008) on the basis of language use in social context whose occurrences were extracted from XIX and XX century advertisements. The phenomenon examined involves constructions consisting of two phrases, which are related to the informational structure Topic/Focus, as in Ice cold pool ... never again, ., showing the following features (i) are common constructions in languages; (ii) require a type of study that does not focus on isolated clauses, since they depend on the communicative situation in which they are used; and (iii) are subjected to intra-clausal rules and principles. The selection of this structure is a user's adaptive strategy to her/his communicative goals in the interaction situation both in terms of pragmatic and semantic formulation and in terms of morphosyntactic and phonological encoding, as predicted by FDG.
Keywords: functional grammar; small clause; nominal phrase; verbless clause